Review paperThe phylogeny of permanent prostate brachytherapy - Aronowitz, Jesse N.; Rivard, Mark J. (Journal of Contemporary Brachytherapy, 2013)
Permanent prostate brachytherapy has been practiced for more than a century. This review examines the influence of earlier procedures on the modern transperineal ultrasound-directed technique. A literature review was conducted to examine the origin of current clinical practice. The dimensions of the modern brachytherapy seed, the prescription dose, and implant/teletherapy sequencing are vestigial features, which may be suboptimal in the current era of low-energy photon-emitting radionuclides and computerized dose calculations. Although the modern transperineal permanent prostate implant procedure has proven to be safe and effective, it should undergo continuous re-evaluation and evolution to ensure that its potential is maximized.